Uma análise das competências em habilidades desenvolvidas nas instituições de ensino superior com base nas normas propostas pelo International Accouting Education Standards Board - IAESB - Vieira, Sandro Rizzon (2024)
The International Accounting Education Standards Board (IAESB) developed international standards aiming to standardize the accountants’ skills development in educational institutions around the world. The IAESB expects that educational institutions, including the Brazilians, promote actions so that these recommendations are achieved during the graduation process of Accounting Sciences students in order to better prepare them for the profession’s challenges. The objective of this research is to investigate whether the in-person Accounting Sciences courses offered in the city of Foz do Iguaçu, in the academics’ perception, are aligned with the technical competencies and professional skills recommended by the IAESB. Therefore, a survey was carried out with final year/period students of two higher education institutions. In data analysis, obtained by carrying out a questionnaire, statistics’ techniques were used such as exploratory factor analysis and descriptive statistics. The results found indicated strong alignment of researched courses to IAESB’s recommendations; on the other hand, the research pointed that are points in the academic’s graduation process that need to be checked.